Evaluasi Program Dana Alokasi Khusus dalam Penanganan Kawasan Kumuh di Kampung Bajo Kelurahan Anaiwoi - Rosnawintang; Adie Rosadi P.; Abd. Azis Muthalib (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to evaluate the Special Allocation Fund program in slum area management activities in Kampung Bajo, Anaiwoi Village, Kolaka Regency. This study uses a qualitative descriptive approach. The informants in the study numbered 10 people consisting of the Kolaka Regency Housing and Settlement Area Service, the Anaiwoi Village Government, and the Bajo Village Community. Data collection used the Focus Group Discussion (FGD) technique. The analysis technique was carried out using the triangulation method through the stages of data collection, data reduction, and drawing conclusions. Based on the results and discussion, it can be concluded that the Special Allocation Fund (DAK) Program in slum area management activities in Kampung Bajo, Anaiwoi Village, Kolaka Regency is administratively in accordance with the Regulation of the Minister of PUPR Number 5 of 2022 concerning Operational Guidelines for Physical Special Allocation Funds for Public Works and Public Housing Infrastructure. The results of slum management are quite beneficial for the people of Kampung Bajo, Anaiwoi Village.